Long term survival after acute myocardial infarction in Australia and New Zealand, 2009‒2015: a population cohort study. Issue 11 (16th May 2021) - Nadlacki, Bora; Horton, Dennis; Hossain, Sadia; Hariharaputhiran, Saranya; Ngo, Linh; Ali, Anna; Aliprandi‐Costa, Bernadette; Ellis, Chris J; Adams, Robert JT; Visvanathan, Renuka; Ranasinghe, Isuru
Abstract: Objective: To assess long term survival and patient characteristics associated with survival following acute myocardial infarction (AMI) in Australia and New Zealand. Design: Cohort study. Setting, participants: All patients admitted with AMI (ICD‐10‐AM codes I21.0‒I21.4) to all public and most private hospitals in Australia and New Zealand during 2009‒2015. Main outcome measure: All‐cause mortality up to seven years after an AMI. Results: 239 402 initial admissions with AMI were identified; the mean age of the patients was 69.3 years (SD, 14.3 years), 154 287 were men (64.5%), and 64 335 had ST‐elevation myocardial infarction (STEMI; 26.9%). 7‐year survival after AMI was 62.3% (STEMI, 70.8%; non‐ST‐elevation myocardial infarction [NSTEMI], 59.2%); survival exceeded 85% for people under 65 years of age, but was 17.4% for those aged 85 years or more. 120 155 patients (50.2%) underwent revascularisation (STEMI, 72.2%; NSTEMI, 42.1%); 7‐year survival exceeded 80% for patients in each group who underwent revascularisation, and was lower than 45% for those who did not. Being older (85 years or older v 18–54 years: adjusted hazard ratio [aHR], 10.6; 95% CI, 10.1–11.1) or a woman (aHR, 1.15; 95% CI, 1.13–1.17) were each associated with greater long term mortality during the study period, as was prior heart failure (aHR, 1.79; 95% CI, 1.76‒1.83). Several non‐cardiac conditions and geriatric syndromes common in these patients were independently associated with lower long term survival, including major and metastatic cancer, cirrhosis and end‐stage liver disease, and dementia. Conclusion: AMI care in Australia and New Zealand is associated with high rates of long term survival; 7‐year rates exceed 80% for patients under 65 years of age and for those who undergo revascularisation. Efforts to further improve survival should target patients with NSTEMI, who are often older and have several comorbid conditions, for whom revascularisation rates are low and survival after AMI poor.